2021
DOI: 10.1111/geb.13431
|View full text |Cite
|
Sign up to set email alerts
|

A hierarchical approach to understanding physiological associations with climate

Abstract: Aim: Our understanding of species' responses to climate depends on choosing the scale for the analysis. Processes driving physiological adaptation that occur at the small spatial scales most relevant to animals may be masked in correlations between organismal traits and broad-scale climatologies, but the extent to which this undermines our understanding of the macroevolution of physiological traits is unknown. Location: Global.Time period: Current.Major taxa studied: Lizards. Methods:We investigated relationsh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 119 publications
1
17
0
Order By: Relevance
“…Our analyses highlight that habitats impose local variability in maximum peak temperature and heat tolerance, not influencing minimum temperature or cold tolerance. This similar contrasting pattern appears in other terrestrial ectotherms (Frishkoff et al 2015, Kaspari et al 2015, Nowakowski et al 2017, Pintanel et al 2019, Anderson et al 2022, Leahy et al 2022. The divergence on the variation of extreme environmental temperatures (i.e.…”
Section: Discussionsupporting
confidence: 69%
“…Our analyses highlight that habitats impose local variability in maximum peak temperature and heat tolerance, not influencing minimum temperature or cold tolerance. This similar contrasting pattern appears in other terrestrial ectotherms (Frishkoff et al 2015, Kaspari et al 2015, Nowakowski et al 2017, Pintanel et al 2019, Anderson et al 2022, Leahy et al 2022. The divergence on the variation of extreme environmental temperatures (i.e.…”
Section: Discussionsupporting
confidence: 69%
“…It is possible that specialisation in abiotically stressful environments such as saline or arid aquatic habitats provides refugee from competition and predation, which are more intense in less stressful habitats (Berdugo et al., 2019; Herbst, 2001). Therefore, a comprehensive understanding of the distribution patterns observed here would need to consider the interactions between biotic interactions and stress tolerance in driving habitat occupation across stress gradients, as well as the role of historical factors (Davis & Scholtz, 2001) and dispersal limitation, and other processes that occur at smaller spatial scales, requiring the use of proximal environmental predictors (Anderson et al., 2021; Schultz et al., 2022).…”
Section: Discussionmentioning
confidence: 99%
“…These results contradicted previous studies (and our macroclimatic analyses) using coarse climatic data that found tropical species to be more vulnerable and perhaps already experiencing body temperatures beyond their upper thermal limits (Clusella‐Trullas et al, 2011; Diamond et al, 2012; Huey et al, 2009). These contradictory results reveal nuances derived from macroclimatic perspectives (Anderson, White, et al, 2022; Logan et al, 2013; Sears et al, 2011; Vasseur et al, 2014). Macroclimatic variables are usually measured at heights, or conditions, that are irrelevant for many animals (Kearney & Porter, 2009; Kearney et al, 2012; Klinges & Scheffers, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…We controlled thermoregulatory behaviour by parametrizing the models with thermal physiological and ecological data collected from the literature (Kearney & Porter, 2020). The ectotherm model can produce highly accurate predictions of body temperature and activity period for lizards, and this approach has been applied in several instances (Anderson, White, et al, 2022; Kearney, 2013; Sunday et al, 2014).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation